Youth political participation: obstacles and pathways to increased youth engagement in the Nigerian political process - Onyewuchi, Chinedu O.; Jawan, Jayum; Ahmad, Zaid (World Textile Information Network, 2024)
This study explores the obstacles and pathways to increased youth engagement in the Nigerian political process focusing on the constraints to youth political participation and the political awareness of young Nigerians. Using semi-structured interviews, a varied sample of 30 youth (18 males and 12 females) from various regions of the country, residing in Lagos, participated in the study. The research identifies key barriers to political participation, including socioeconomic challenges, low political awareness, political disillusionment, lack of access to political platforms, and systemic corruption. The study also uncovered pathways that could facilitate greater youth involvement, such as improved civic education, increased use of social media for political mobilization, youth-targeted policies, and mentorship opportunities within political organizations. Participants highlighted the importance of youth inclusion in decision-making processes and reforms aimed at addressing youth-specific concerns. The findings suggest that, despite the obstacles, there is significant potential for increased youth engagement in Nigerian politics if structural changes and targeted interventions are implemented. This research contributes to the discourse on youth empowerment and democratic participation in emerging democracies.